2019
DOI: 10.1016/j.tranon.2018.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Chemotherapeutic Profiling of Gynecologic Cancer Cell Lines Using Approved Drugs and Bioactive Compounds

Abstract: Heterogeneous response to chemotherapy is a major issue for the treatment of cancer. For most gynecologic cancers including ovarian, cervical, and placental, the list of available small molecule therapies is relatively small compared to options for other cancers. While overall cancer mortality rates have decreased in the United States as early diagnoses and cancer therapies have become more effective, ovarian cancer still has low survival rates due to the lack of effective treatment options, drug resistance, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 87 publications
(77 reference statements)
1
7
0
Order By: Relevance
“…Two studies showed that fedratinib in combination with erlotinib (EGFR tyrosine kinase inhibitor) decreased STAT3 activation and increased apoptosis in erlotinib-resistant NSCLC cells and inhibited tumor growth in in vivo murine models [155,156] . This agent has also demonstrated cell-killing activity against ovarian and cervical cancer cells [157] . Fedratinib inhibited mammosphere formation and in combination with carboplatin, inhibited breast cancer tumor growth in mice [158] .…”
Section: Fedratinibmentioning
confidence: 99%
“…Two studies showed that fedratinib in combination with erlotinib (EGFR tyrosine kinase inhibitor) decreased STAT3 activation and increased apoptosis in erlotinib-resistant NSCLC cells and inhibited tumor growth in in vivo murine models [155,156] . This agent has also demonstrated cell-killing activity against ovarian and cervical cancer cells [157] . Fedratinib inhibited mammosphere formation and in combination with carboplatin, inhibited breast cancer tumor growth in mice [158] .…”
Section: Fedratinibmentioning
confidence: 99%
“…Ultimately, coordination of copper with the elesclomol ligand disrupts the production and metabolism of cellular energy and triggers the path of mitochondrial apoptosis in tumor cells, leading to their death [44]. An antitumor activity of the redox-active copper coordination compound was also confirmed in [45], where the potential effectiveness of elesclomol in treating ovarian cancer was shown. The elesclomol ligand showed antiproliferative activity on six cell lines of gynecological cancer with an IC50 of 0.173 µ M and an IC90 of 0.283 µ M (tests were performed with Cu-preincubated cell lines).…”
Section: N-and S-donor Ligandsmentioning
confidence: 99%
“…Entinostat (15) Inhibition of HDACs 1, 2, 3, and 9 Entinostat presented anti-proliferative activity in vitro and in vivo against several cancer lines, including cervical cancer and a panel of gynecologic cell lines. (Saito et al, 1999;Lauffer et al, 2013;Gorshkov et al, 2019) HDAC1 19) presented an activity against HeLa cells and IC 50 value of 0.92 mM and increased intracellular levels of ROS after treatment with a concentration of 0.8 mM. (Oca et al, 2018;Sixto-López et al, 2020) HDAC1:153.78 µM HDAC6:>1000 µM HDAC8:>1000 µM Luotonin A derivative (20) Inhibition of HDAC 1 and 2 Compound (20) presented an antiproliferative activity against HeLa cells identical to Luotonin A, its precursor; however, the selective index was 4.4 times superior for the synthesized compound compared to Luotonin A.…”
Section: -Aminobenzamide Derivativesmentioning
confidence: 99%